Metabolic comparison of minimally to noninvasive urogenital sample types for studying gynecologic health: A pilot study - Holly Chatenoud; Paweł Łaniewski; Nichole D. Mahnert; Melissa M. Herbst-Kralovetz (iScience)
Summary: In this pilot study, we investigated three minimally to noninvasive biospecimens: cervicovaginal lavages (CVLs), vaginal swabs, and urine, from 18 premenopausal women using untargeted metabolomics to inform future gynecologic research. Metabolic profiles were compared between specimen types and between participants grouped based on vaginal microbiome composition and body mass index (BMI). We identified metabolites altered in the groups in all sample types; however, different metabolites were uniquely detected in each biospecimen. Within CVLs, key amino acid signatures (i.e., polyamines) were identified in women with dysbiosis. While polyamines were also detected in vaginal swabs, this sample type exhibited more lipid signatures. In urine, we specifically detected estrogenic steroids, endocrine-disrupting compounds, and certain drugs. Overall, each urogenital biospecimen type exhibits unique metabolic profiles and, based on metabolic alteration in the context of vaginal microbiome and BMI, can be valuable tools in answering questions related to gynecologic health.